2020
DOI: 10.1074/jbc.ra119.010535
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic deficiency of transferrin receptor 2 is associated with increased erythropoiesis independent of iron overload

Abstract: Transferrin receptor 2 (TFR2) is a transmembrane protein expressed mainly in hepatocytes and in developing erythroid cells and is an important focal point in systemic iron regulation. Loss of TFR2 function results in a rare form of the iron-overload disease hereditary hemochromatosis. Although TFR2 in the liver has been shown to be important for regulating iron homeostasis in the body, TFR2's function in erythroid progenitors remains controversial. In this report, we analyzed TFR2-deficient mice in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A delayed differentiation of human primary erythroblasts knocked down for TFR2 expression and a decreased sensibility to Epo of murine erythroid progenitors CFU-E from Tfr2 −/− mice were observed [ 10 ]. Following this study, contradictory observations were made in mouse models, with the knockout of Tfr2 leading either to a greater production of RBCs [ 57 , 58 ], or to a decreased production [ 59 , 60 ]. Recently, several studies explored the effect of erythroid Tfr2 deletion in bone-marrow specific deletion models with once again varying results.…”
Section: Signaling Of the Transferrin Receptors And Erythropoiesismentioning
confidence: 99%
“…A delayed differentiation of human primary erythroblasts knocked down for TFR2 expression and a decreased sensibility to Epo of murine erythroid progenitors CFU-E from Tfr2 −/− mice were observed [ 10 ]. Following this study, contradictory observations were made in mouse models, with the knockout of Tfr2 leading either to a greater production of RBCs [ 57 , 58 ], or to a decreased production [ 59 , 60 ]. Recently, several studies explored the effect of erythroid Tfr2 deletion in bone-marrow specific deletion models with once again varying results.…”
Section: Signaling Of the Transferrin Receptors And Erythropoiesismentioning
confidence: 99%
“…27 Furthermore, using a systemic TFR2 deficient mouse model, Wortham et al recently showed that extrahepatic (bone marrow and spleen) TFR2 deficiency was associated with increased erythropoiesis, independent of iron overload. 28 The preferential orientation, in iron deficiency, toward the production of platelets instead of red blood cells remains to be explained. This regulatory mechanism may, on a chronic basis, preserve the use of iron for functions other than erythroid differentiation and, in acute clinical situations, help stop a life-threatening hemorrhage.…”
Section: Role Of Iron In Platelet Formationmentioning
confidence: 99%
“…Nevertheless, it has been shown that specific bone marrow TFR2 loss of function stimulates erythropoiesis without causing systemic body iron excess 27 . Furthermore, using a systemic TFR2 deficient mouse model, Wortham et al recently showed that extrahepatic (bone marrow and spleen) TFR2 deficiency was associated with increased erythropoiesis, independent of iron overload 28 . The preferential orientation, in iron deficiency, toward the production of platelets instead of red blood cells remains to be explained.…”
Section: Iron and Platelets: General Aspectsmentioning
confidence: 99%
“…In contrast, hematopoietic-specific ablation of the Tfr2 gene in mice enhances erythropoiesis, likely by modulating EPO sensitivity 102 . Expression of TFR2 in the kidney may inhibit EPO production 103 . Interaction with iron-bound transferrin stabilizes TFR2 at the cell surface 104 , representing a potential mechanism by which TFR2 coordinates erythropoietic rate and enteral iron uptake with circulating iron level.…”
Section: Epo Activities Are Mediated Through the Epormentioning
confidence: 99%